Psychological safety as a mediating variable in the relationship between ethical leadership and employee engagement at work. - Hendler, Dina (My University, 2012)
Given the prevailing ethical crisis and subsequent collapse of a number of modern organizations, the lapse in leader ethics as a determining factor of the proliferation of corrupt practices has come to dominate leadership discourse. Ethical leadership has been linked not only to avoiding organizational destruction but to fostering healthy, productive organisations. In line with this, the current study aimed to assess the role of employee perceptions of ethical leadership in promoting employee engagement, via the mediating mechanism of employee perceptions of psychological safety.. Having distributed an email survey to administrative employees of a technological goods producer, Kalshoven et al.’s (2011) Ethical leadership at Work scale, Carmeli and Gittel’s (2009) psychological safety scale and the 17-item version of Utrecht’s employee engagement scale (Schauefeli & Bakker, 2003) were completed by 139 participants. Using structural equation modelling, the findings supported the linkage between ethical leadership and employee engagement and confirmed the role of psychological safety in mediating this relationship.
Keywords: Ethical leadership; Employee engagement; Psychological safety